2001
DOI: 10.1073/pnas.261359098
|View full text |Cite
|
Sign up to set email alerts
|

The role of the third β strand in gp120 conformation and neutralization sensitivity of the HIV-1 primary isolate DH012

Abstract: Neutralization of HIV-1 primary isolates has been a tremendous challenge for AIDS vaccine development. Here, we identify a single amino acid change (T198P) in gp120 that alters the neutralization sensitivity of the primary isolate DH012 to antibodies against multiple neutralization epitopes that include the V3, CD4-induced, and CD4 binding sites in gp120. This mutation is located in the V1͞V2 stem region that forms the third ␤ strand (␤3) of the bridging sheet of gp120. The conformation of variable loops, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
3
23
1
Order By: Relevance
“…The inhibitory effect of the JR-FL V1/V2 domain on neutralization is consistent with a number of previous studies showing that mutations or deletions in the V1/V2 region of several cloned HIV-1 env genes can affect the sensitivity of those strains to neutralization by antibodies against multiple domains (5,47,54). Other studies indicated that for the SIVmac239 isolate, the V1/V2 region was a major factor inducing resistance to neutralization (23).…”
Section: Discussionsupporting
confidence: 89%
“…The inhibitory effect of the JR-FL V1/V2 domain on neutralization is consistent with a number of previous studies showing that mutations or deletions in the V1/V2 region of several cloned HIV-1 env genes can affect the sensitivity of those strains to neutralization by antibodies against multiple domains (5,47,54). Other studies indicated that for the SIVmac239 isolate, the V1/V2 region was a major factor inducing resistance to neutralization (23).…”
Section: Discussionsupporting
confidence: 89%
“…In particular, it has been shown that 17b diminishes the affinity of sCD4 for gp120 by decreasing the on rate and increasing the off rate (93), despite the fact that sCD4 clearly increases the affinity of 17b to gp120. Zhu et al proposed a model in which the V1/V2 and V3 loops interact, and this interaction is disrupted by a particular mutation (T198P) in the bridging sheet (94). Our results show that the T198P mutation reduces 4KG5 binding, consistent with the idea that this mutation may disrupt an interaction between V1/V2 and V3.…”
supporting
confidence: 89%
“…c A T198P substitution was previously determined to affect the interaction between the V1/V2 and V3 loops (94).…”
mentioning
confidence: 99%
“…Recently, Zhu et al showed that an engineered molecule (MBri) containing the V1/V2 loop and a portion of the bridging sheet of gp120 (i.e., ␤2, ␤3, ␤20, and ␤21) was able to bind to b12 (91). These authors showed that a V3 loop peptide is able to partially inhibit the binding of b12 to MBri and attributed this effect to a physical interaction between the V1/V2 loop and V3 loop.…”
Section: Discussionmentioning
confidence: 99%